Rice Farmers' Rationality and Adaptation to Double Pressure: Input Price Increases and Grain Price Fluctuations in Indramayu Regency - Faizatun Khasanah; Salsabila Anisa Sirrinqoufin; Farida Mardhatilla; Nurul Arifah Fauzi (Jurnal Agrosci, 2025)
Background: Indramayu Regency contributes significantly to rice production, facing a serious challenge, namely double pressure. Increase in production input prices (seeds, fertilizers, pesticides, labor) and fluctuations in grain prices that tend to suppress profit margins. This study aims to explore the form of farmers' rationality to the influence of double pressure and identify the adaptations applied by farmers in managing risks and responding to realities in the field. Method: A descriptive qualitative approach of data collected through in-depth interviews, observations, and documentation in five main sub-districts, and then analyzed with Miles and Huberman's interactive model with source triangulation techniques to strengthen the validity of the data. Results: Indicate that profit-loss calculations, limited access to production resources, local social networks, and historical farming experience contextually influence farmers' rationality. Farmer adaptation also reveals the emergence of ecological and institutional dimensions, which are grounded in local experiences and community innovation. Conclusion, farmers in Indramayu not only survive but also transform the face of double pressures, demonstrating complex rationality and multidimensional adaptation